2004
DOI: 10.1002/sia.1980
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of poly(ether sulphone) Part 1. A time‐of‐flight secondary ion mass spectrometry study

Abstract: An extensive study of the surface chemical changes to poly(ether sulphone) (PES) ultrafiltration membranes is made for the first time by the use of time-of-flight secondary ion mass spectrometry (ToF-SIMS) after photoirradiation at 254 nm with irradiances varying from 10 to 300 mJ cm −2 in a nitrogen atmosphere. Complementary information is provided by analysis with x-ray photoelectron spectroscopy (XPS) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). The versatility, super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…Nevertheless, -SO 3 H groups appear to be formed in a nitrogen atmosphere, suggestive of incomplete removal of ambient air, i.e. residual oxygen reacts with the -SO 2 ž radicals formed on the PES surface (consistent with conclusions made in the preceding article 8 ). This agrees with the fact that the SO 3 intensity curve for nitrogen lies between the curves for a vacuum and air.…”
Section: Formation Of -So 3 H Groupssupporting
confidence: 80%
See 3 more Smart Citations
“…Nevertheless, -SO 3 H groups appear to be formed in a nitrogen atmosphere, suggestive of incomplete removal of ambient air, i.e. residual oxygen reacts with the -SO 2 ž radicals formed on the PES surface (consistent with conclusions made in the preceding article 8 ). This agrees with the fact that the SO 3 intensity curve for nitrogen lies between the curves for a vacuum and air.…”
Section: Formation Of -So 3 H Groupssupporting
confidence: 80%
“…In the preceding article 8 it was suggested based on ToF-SIMS data that -SO 3 H groups are formed as a consequence of photoirradiation and reaction with residual oxygen. In Fig.…”
Section: Formation Of -So 3 H Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV-induced modification stands out among all the surface modification techniques developed to improve PES surface properties for many applications due to its simplicity, usefulness, versatility, and low cost, which make its use very widespread. Other researchers have demonstrated that all polyarylsulfone materials are intrinsically photosensitive at a wavelength higher than 254 nm [7,10]. Its main advantage is the ability to modify different properties on the PES surface by introducing functional groups from the selected monomer (or monomers) or by entrapping inorganic nanoparticles without affecting the bulk properties [7,11].…”
Section: Introductionmentioning
confidence: 99%